SAT0058 Using the Multi-Biomarker Disease Activity Score as a Complementary Inclusion Criterion for Clinical Trials in Rheumatoid Arthritis May Enhance Recruitment. (10th June 2014) - van Vollenhoven, R.F.; Bolce, R.; Hambardzumyan, K.; Saevarsdottir, S.; Forslind, K.; Ernestam, S.; Petersson, I.F.; Sasso, E.H.; Hwang, C.C.; Segurado, O.G.; Geborek, P.
Abstract : Background: Clinical trials in rheumatoid arthritis (RA) often require elevated C-reactive protein (CRP), e.g., >10 mg/L, to enhance detection of clinical and radiographic efficacy. However, this inclusion criterion may limit recruitment by excluding some patients with active disease. The multi-biomarker disease activity (MBDA) score quantifies disease activity with a score of 1 to 100 and can be high (>44) even when the CRP is ≤10 mg/L. Objectives: To explore the hypothesis that, by using MBDA score >44 as a clinical trial inclusion criterion complementary to CRP>10mg/L, the number of eligible patients can be increased while maintaining the ability to detect treatment responses. Methods: In the SWEFOT trial, DMARD-naïve patients with early RA were enrolled, without a CRP requirement, and received methotrexate (MTX) monotherapy from baseline; at 3 months, non-responders to MTX (NR, DAS28>3.2) received treatment intensification. We analyzed: 1) Patients from baseline to 3 months, and 2) MTX non-responders; for the latter population we used data from month 3 as the de facto baseline and changes from month 3 to 12 as the measured response. In both analyses patients were grouped according to CRP (≤10 vs. >10 mg/L) or MBDA score (≤44 vs. >44) and assessed for clinical outcomes from baseline to 3 months following treatment with MTX, and from 3 to 12 months for add-on therapy (triple therapy or anti-TNF). Radiographic progression was assessed by change in SHS from baseline to 1 year for both analyses. Results: For the DMARD-naïve population (N=220), baseline values and changes from baseline for disease activity measures and ΔSHS were similar for patients with CRP >10 mg/L versus MBDA score >44. Moreover, by adding the 37 patients with MBDA score >44 and CRP ≤10 mg/L to the group with CRP >10 mg/L (N=154), the combined group (N=191) had 24% more patients and similar clinical and radiographic outcomes. Similarly, for the MTX non-responder population (N=127), values at month 3 and changes to month 12 were similar for the CRP >10 mg/L and MBDA >44 groups, and adding the 23 patients with month 3 MBDA score >44 and CRP ≤10 mg/L to the group with CRP >10 mg/L (N=49) created a combined group (N=72) with 47% more patients and similar outcomes. The results are summarized in the table. Conclusions: These data suggest that if a clinical trial of DMARD-naïve or MTX-non-responder patients were to include all patients with MBDA score >44 and/or CRP >10 mg/L, the number of eligible patients can be increased by 24% and 47%, respectively, compared with enrollment based on CRP >10 mg/L alone, while maintaining clinical and radiographic outcomes. Disclosure of Interest: R. van Vollenhoven Grant/research support: AbbVie, BMS, GSK, Pfizer, Roche, UCB, Consultant for: AbbVie, Biotest, BMS, Crescendo, GSK, Janssen, Lilly, Merck, Pfizer, Roche, UCB, Vertex, R. Bolce Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, K. Hambardzumyan: None declared, S. Saevarsdottir: None declared, K. Forslind: None declared, S. Ernestam: None declared, I. Petersson Speakers bureau: UCB Phama, Pfizer, AbbVie, E. Sasso Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, C. Hwang Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, O. Segurado Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, P. Geborek: None declared DOI: 10.1136/annrheumdis-2014-eular.3329